Edible and Medicinal Mushrooms: Emerging Brain Food for the Mitigation of Neurodegenerative Diseases - Phan, C.W.; David, P.; Sabaratnam, V. (Mary Ann Liebert, 2017)
There is an exponential increase in dementia in old age at a global level because of increasing life expectancy. The prevalence of neurodegenerative diseases such as dementia and Alzheimer's disease (AD) will continue to rise steadily, and is expected to reach 42 million cases worldwide in 2020. Despite the advancement of medication, the management of these diseases remains largely ineffective. Therefore, it is vital to explore novel nature-based nutraceuticals to mitigate AD and other age-related neurodegenerative disorders. Mushrooms and their extracts appear to hold many health benefits, including immune-modulating effects. A number of edible mushrooms have been shown to contain rare and exotic compounds that exhibit positive effects on brain cells both in vitro and in vivo. In this review, we summarize the scientific information on edible and culinary mushrooms with regard to their antidementia/AD active compounds and/or pharmacological test results. The bioactive components in these mushrooms and the underlying mechanism of their activities are discussed. In short, these mushrooms may be regarded as functional foods for the mitigation of neurodegenerative diseases.